PENAL MEDIATION AS ALTERNATIVE DISPUTE RESOLUTION IN PAREPARE - Andi Marlina (IAIN Bone, 2020)
The purpose of this study is to analyze the penal mediation that does not aim to achieve formal justice and the practice of penal mediation at the Parepare Police Department. The research method is normative legal research, using a statute and conceptual approach. The collected legal materials are then analyzed qualitatively, then presented descriptively. The results showed that the dimension of mediation of the penalties achieved was not formal justice through the Criminal Justice sub-system regulated in formal legal regulations. From a juridical perspective, mediation of penalties in the dimensions of state law (ius constitutum) is actually not well known and still leaves controversy among those who agree and disagree to be applied. The essential issue leads to the choice of a pattern of criminal dispute resolution, related to the domain of state superiority with the superiority of the local wisdom community. The practice of mediating penalties at the Parepare Police Department in the last 3 years (2017, 2018 and 2019) the number of criminal cases every year has always increased in number, as well as the mediation of cases conducted by the Manokwari Police Department each year experiencing an increase in the number of criminal cases being mediated.